2020
DOI: 10.3390/su12072964
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Spatial and Temporal Relationship between Air Quality and Urban Land-Use Patterns Based on an Integrated Method

Abstract: The deterioration of air quality in urban areas is often closely related to urbanization, as this has led to a significant increase in energy consumption and the massive emission of air pollutants, thereby exacerbating the current state of air pollution. However, the relationship between urban development and air quality is complex, thus making it difficult to be analyzed using traditional methods. In this paper, a framework integrating spatial analysis and statistical methods (based on 170 regression models) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…A negative correlation was found between spatial patterns of green spaces, including dense trees (A), scattered trees (B), bush and scrub (C), and low plants (D), and the pollutants NO 2 , SO 2 , and CO. In line with the ndings of the study by Ku (2020), the investigation of the spatial con guration of such land uses showed that the increased PD of trees led to a reduced concentration of pollutants. This can be due to increased evapotranspiration and more photosynthesis in trees than other plants (Cao et al, 2010;Lin & Xu, 2016;Zhang et al, 2009).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…A negative correlation was found between spatial patterns of green spaces, including dense trees (A), scattered trees (B), bush and scrub (C), and low plants (D), and the pollutants NO 2 , SO 2 , and CO. In line with the ndings of the study by Ku (2020), the investigation of the spatial con guration of such land uses showed that the increased PD of trees led to a reduced concentration of pollutants. This can be due to increased evapotranspiration and more photosynthesis in trees than other plants (Cao et al, 2010;Lin & Xu, 2016;Zhang et al, 2009).…”
Section: Discussionsupporting
confidence: 74%
“…They showed a positive correlation between spatial trends of air pollutants with the density of built-up land in Guangzhou, China. Also, Ku (2020) have illustrated that the annual averages NO 2 is increased by increase of built-up area in Tiachung city, Taiwan. Whereas inverse relationship was observed between the increase in forest connectivity and forest area and annual average of NO 2 .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Thus, it takes an active role from the government and society to deal with these problems. Furthermore, to ensure the sustainability of the urban environment, urban planning is an instrument used to formulate countermeasures for the government [104]. Furthermore, the direct and indirect effects of urban activity systems, transportation systems, and origin-destination movement patterns on environmental quality degradation and air pollution index are described in Figure 12 below.…”
Section: Traffic Volume and Decreasing Environmental Qualitymentioning
confidence: 99%
“…Early land use/cover change studies have utilized historical records and hand-drawn maps to depict arable land in arid regions [5,6]. Since the 1990s, land use/cover maps from remotely sensed images have been employed as the main data source to monitor the arable land's status and its response to external disturbance [7][8][9], because remotely sensed images can help retrieve the context, direction, and rate of arable land change in a time-and labor-saving way [10,11]. According to the spatial resolution, remotely sensed images can be categorized to coarse-, middle-and high-resolution classes.…”
Section: Introductionmentioning
confidence: 99%